PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION)PELAJARAN IPS PADA SISWA KELAS VI SD 166325 TEBING TINGGI - Rosdiana Br. Sinaga (Universitas Negeri Medan, 2019)
This purposes of this research is to improve learning result on Social Sciences subject through CIRC method. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students fromgrade VI, Elementary Schoold State 166325 Tebing Tinggi which amounted to 35 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the CIRC method of social sciences subject can improve student learning result characterized by increased mastery learning students that cycle I (77,14%), cycle II (91,42 %) and complete learn the clasical equal to 91,42%. Keywords : CIRC, social sciences, learning outcomes.